Regulatory sites for splicing in human basal ganglia are enriched for disease-relevant information - Sebastian Guelfi (Nature Portfolio, 2020)
Regulation of gene expression and splicing are thought to be tissue-specific. Here, the authors obtain genomic and transcriptomic data from putamen and substantia nigra of 117 neurologically healthy human brains and find that splicing eQTLs are enriched for neuron-specific regulatory information.